KAJIAN ANTROPOLOGI SASTRA DAN NILAI PENDIDIKAN DALAM CERITA RAKYAT KALANTIKA SERTA RELEVANSINYA SEBAGAI BAHAN AJAR DI SMP - Nurfitriana Maulidiah; Suyitno Suyitno; Slamet Mulyono (Universitas Sebelas Maret, 2018)
This research is proposed to describe and explain; (1) the themes in folktale Kalantika, (2) the cultural features in activities of folktale’s figure Kalantika, (3) the cultural result in folktale Kalantika, (4) the education value in set of folktale Kalantika,(5) the relevance of set of folktale Kalantika with learning in Junior High School. This research used descriptive qualitative method with literary anthropology approach. Sampling technique that used in this research is purposive sampling. Collecting data technique use document analysis and interview. To validity the data, it uses triangulation of source. Data analysis technique in this research uses interactive analysis techniques. The results of this research shows that: (1) the themes of a set of folktale Kalantika were ideas about the human view of universe and knowledge system; (2) the cultural characteristic in activities of folktale’s figure Kalantika were activities about equipment of human life, livelihood system, and knowledge system; (3) the cultural result of set of folktale Kalantika that can be find are the cultural result in the form of livelihood system and economy system, and knowledge system also; (4) education value that can be find are moral value, social value, religion value, and culture value; (5) Kalantika can be some teaching materials in literary learning of Junior High School.